Pengaruh Pengembangan SDM, Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Tabta Sukses Abadi - Trengginas, Satriodimas Lantip; Waruwu , Ahmad Aswan; Yanti, Eli Delvi (Indo-MathEdu Intellectuals Journal, 2025)
The research aims to analyze the influence of human resource development, leadership style, and work motivation on employee performance at PT Tabta Sukses Abadi. The data analysis technique used is associative research methods with the help of SPSS version 25. This study uses multiple linear regression analysis. The sample for this study consisted of 76 respondents. Primary data was collected using a questionnaire. The data analysis technique employed multiple linear regression analysis. The research results show that testing for the human resource development variable indicates that human resource development positively and significantly affects the performance of employees at PT Tabta Sukses Abadi. Leadership style has a positive and significant partial effect on employee performance at PT Tabta Sukses Abadi. Work motivation also has a positive and significant partial effect on employee performance at PT Tabta Sukses Abadi. The calculated F value is 110.479, which is greater than 2.71 and the significance value is 0.000, which is smaller than 0.05, thus it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected, thereby concluding that human resource development, leadership style, and work motivation have a significant simultaneous effect on the performance of employees at PT Tabta Sukses Abadi.